Free trade with Mexico. - Morici, Peter (1992)
Discusses the potential of free trade between the US and Mexico to catalyze, solidify, and intensify forces that could transform the US and Mexican economies. Notes that for the US, a free trade agreement could be a key element in a new national strategy to foster competitiveness. For Mexico, free trade would mark the climax of a radical change in development strategy.